Temporalidades urbanas na Ribeira, Natal/RN: entre derivas, passagens e montagens - Pereira, Arthur Leonardo de Lima (2022)
Resulting from an intense ethnographic work carried out between the years 2020 and 2021, this research is conducted from my position as anthropologist-photographer, within the Núcleo de Antropologia Visual from Universidade Federal do Rio Grande do Norte (NAVIS/UFRN), in research on images, itineraries and memories of the Historic Center of Natal, having the neighborhood of Ribeira as our space-time cut. We position ourselves from Visual and Urban Anthropology by opening a space in the testimony for the inscription of other stories, in the debate about memory disputes in the intention of reassembling and reopening the stories of this neighborhood from a very particular moment, Manoel Dantas’ Conference Natal D’aqui a cincoenta annos (Natal fifty years from now, 1909) and the desire of the Natal elite to include Natal in the paths of progress and capitalist modernity. Such project is evoked through images, which, beyond archival records, are constituted as a way of reflecting the material reality for the city. We ask ourselves about which movements are distinctive in the sense of weaving a reflection about the incorporation of a modernity project in Natal, as an integrant part, not of a Eurocentered history, of the winners, but one thought from the memory of the losers, of Latin America. In order to see the consequences of these processes manifested in the city-image, we carried out ethnographic walks through the city, in which we are affected by a sense of strangeness, when we notice in its architecture the traces of this modern project in the ruins that make the passages of memories from the past to the present. It is necessary, therefore, to exercise a sensitive listening-eye that tells us what the city tells us about as it retells its stories and what the consequences of its transformations are for its future and its people. It is about drifting along the tiles of the alleys, trails of yesteryear that reveal paths that are spatially accessible but temporally unreachable. In order to carry out this research, we used methodological procedures such as walks and drifts in the city, visual records, archive research, and photographic montages. The theoretical analyses followed the principles and tools of urban and audiovisual anthropology, using the concepts of montage, photobiography and imagememory, ruins and dialectics of history. The images inhabit a past-present that reaches us in our time and drives its project to our present-future. This perspective evokes a process of ruining, where ruins are this manifest encounter, the materialization of contradictions structuring the city founded by the projects of western capitalist modernity.